Emerging advances in drug delivery systems (DDSs) for optimizing cancer complications - Kerui Li; Bei Guo; Junmou Gu; Na Ta; Jia Gu; Hao Yu; Mengchi Sun; Tao Han (Materials Today Bio)
The management and treatment of tumor complications pose continuous challenges due to the inherent complexity. However, the advent of drug delivery systems (DDSs) brings promising opportunities to address the tumor complications using innovative technological approaches. This review focuses on common oncological complications, including cancer thrombosis, malignant serous effusion, tumor-associated infections, cancer pain, and treatment-related complications. Emphasis was placed on the application and potential of DDSs in mitigating and treating these tumor complications, and we delved into the underlying mechanisms of common cancer-associated complications, discussed the limitations of conventional treatments, and outlined the current status and potential development of DDSs for various complications in this review. Moreover, we have discussed the existing challenges in DDSs research, underscoring the need for addressing issues related to biocompatibility and targeting of DDSs, optimizing drug delivery routes, and enhancing delivery efficiency and precision. In conclusion, DDSs offer promising avenues for treating cancer complications, offering the potential for the development of more effective and safer drug delivery strategies, thereby improving the quality of life and survival rates of cancer patients.